THE RELATIONSHIP OF KNOWLEDGE AND MOTHER MOTIVATION LEVEL WITH NUTRITION STATUS IN PRESCHOOL AGE CHILDREN 3-6 YEARS AT PUSKESMAS KEMIRI TANGERANG DISTRICT - Fitri, Juliani; Sartika, Rini (Journal of Vocational Nursing, 2021)
Introduction: Nutrition and health problems characterized by the use of unbalanced food are significant problems for most of the population, including children. In the world and in Indonesia, they are experiencing environmental challenges due to the 3 burdens of malnutrition which may worsen due to the Covid-19 pandemic. Children can face various kinds of malnutrition due to poor eating patterns, parenting applications that are not optimal. The government has determined stunting as one of the priority programs. Preschool-aged children are included in the nutritionally vulnerable group of people, namely the group of people who are most susceptible to nutritional disorders, while at this time they are experiencing a relatively rapid growth process. One of the significant aspects that affect the nutritional status of children is the aspect of mother's knowledge about nutrition in children. Objective : This study aims to determine the level of knowledge of the relationship between the level of knowledge and motivation of mothers about balanced nutrition with nutritional status in preschool children aged 3-6 years. Methods: This research is quantitative in nature using correlational descriptive techniques with a cross sectional approach. The population in this study was 100 people and the number of samples taken using the Slovin formula was 80 people using purposive sampling technique. This study uses univariate and bivariate analysis with Chi Square test. Results: based on univariate analysis of 80 people the majority with a high level of knowledge as many as 61 people (76.3%), sufficient motivation as many as 62 people (77.5%) and nutritional status normal children as many as 37 children (46.3%). The results of the bivariate analysis with the chi square test were obtained for the level of knowledge with nutritional status p-value 0.026, and the results of the bivariate analysis of mother's motivation with nutritional status p-value 0.006, it can be concluded that there is a relationship between the level of knowledge and motivation of mothers about balanced nutrition with the nutritional status of children aged preschool 3-6 years. Conclusion: there is a relationship between the level of knowledge and motivation of mothers about balanced nutrition with the nutritional status of preschool children aged 3-6 years.